THE UNDERSTANDING OF LOGIC AND LANGUAGE - Mirzaakbarov, Sulton (Журнал иностранных языков и лингвистики, 2021)
This article seeks to show the connections and differences between language and logic. Basically, about what logic is, what language is and how they are completely applied with an adequate effort.